Design, synthesis, biological evaluations and in silico studies of N-substituted 2,4-thiazolidinedione derivatives as potential a-glucosidase inhibitors - Dahiya L.; Kumar R.; Baidya A.T.K.; Kumar S.; Kumar R.; Pawar S.V.; Yadav A.K. (My University, 2025)
Diabetes mellitus is considered as one of the principal global health urgencies of the twenty first century. In the present investigation, novel N-substituted 2,4-thiazolidinedione derivatives were designed, synthesized, and characterized by spectral techniques. All the newly synthesized N-substituted 2,4-thiazolidinedione derivatives were tested for in vitro α-glucosidase inhibitory activities and compounds A-12 and A-14 were found to be the most potent which were further subjected to in-vivo disaccharide loading test. The most potent compound was also found to be non-toxic in cytotoxicity studies. Further, docking studies were carried out to investigate the binding mode and key interactions with amino acid residues of α-glucosidase. Molecular dynamic simulations studies for the compounds acarbose, A2, A12, and A14 were done with α-glucosidase protein. Further, ΔG was calculated for acarbose, A2, A12, and A14. In silico studies and absorption, distribution, metabolism, excretion (ADME) prediction studies were also executed to establish the ‘druggable’ pharmacokinetic profiles. Here, we have developed novel N-substituted TZD analogues with different alkyl groups as α-glucosidase inhibitors. Communicated by Ramaswamy H. Sarma. © 2023 Informa UK Limited, trading as Taylor & Francis Group.